SISTEM KEKERABATAN ( PARTUTURAN ) MARGA BATAK TOBA PADA KOMUNITAS MAHASISWA BATAK TOBA DI PEKANBARU - Hermanto Naibaho; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In the Toba Batak tribe community, especially Batak Toba students partuturan marga very important as determining the kinship system. The partuturan also serves as a bridge in the implementation of adat rules of Dalihan Na Tolu in the Toba Batak community. Partuturan marga is considered important for the Toba Batak community is who we are at Dalihan Na Tolu. Partuturan marga with clan diversity  is ideal for the Toba Batak tribe to look for clan kinship which is a matchmaking tradition from ancient times until now although it is a simple thing but this could be happen, because in principle the Bataknese, clan becomes self-identity, if you have a same clan but not as blood, thats could be called as a brotherhood, but if it's blood but not one clan then that can be questioned. The subjects of this research were 8 people where the subject of this study is Parsinabung and chair of the community clan college student, and students who are doing activities in Pekanbaru city. The technique of determining informants in this study is using purposive sampling technique. The research method used is descriptive qualitative research method. The theory used is the Symbolic Interaction theory proposed by Ralph Larossa and Donald C. Reitzes (1993) in the West-Turner. The results of the research can be concluded that understanding of Partuturan Marga Batak Toba at The Toba Batak Student Community in Pekanbaru is the most valueable because process in Attracting the Clan Kinship Systems, The Toba Batak tribe must be based on Partuturan Marga , but this tradition has begun to be erroneous with the development of technology and science. Keywords : Partuturan Marga Toba Batak, Symbolic interactionism.